Redirection of the immune response to the functional catalytic domain of cruzipain improves protective immunity against Trypanosoma cruzi infection - Cazorla, Silvia Ines (2010)
Despite the strong immune responses elicited after natural infection with Trypanosoma cruzi or vaccination against it, parasite survival suggests that these responses are insufficient or inherently inadequate. T. cruzi contains a major cystein proteinase, cruzipain, which has a catalytic N-terminal domain and a C-terminal extension. Immunizations that employed recombinant cruzipain or its N- and C-terminal domains allowed evaluation of the ability of cruzipain to circumvent responses against the catalytic domain. This phenomenon is not a property of the parasite but of cruzipain itself, because recombinant cruzipain triggers a response similar to that of cruzipain during natural or experimental infection. Cruzipain is not the only antigen with a highly immunogenic region of unknown function that somehow protects an essential domain for parasite survival. However, our studies show that this can be reverted by using the N-terminal domain as a tailored immunogen able to redirect host responses to provide enhanced protection.